2019
DOI: 10.1016/j.jdiacomp.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for readmission of inpatients with diabetes: A systematic review

Abstract: We have limited understanding of which risk factors contribute to increased readmission rates amongst people discharged from hospital with diabetes. We aim to complete the first review of its kind, to identify, in a systematic way, known risk factors for hospital readmission amongst people with diabetes, in order to better understand this costly complication. Method The review was prospectively registered in the PROSPERO database. Risk factors were identified through systematic review of literature in PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 64 publications
4
8
0
2
Order By: Relevance
“…This is the first SR with MA to demonstrate that gender, age, race, health insurance type, comorbidities including heart failure, respiratory disease, depression and renal disease, LOS as well as use of insulin therapy were significantly associated with 30-day unplanned hospital readmission. Our findings are consistent with those reported in a recent SR by Robbins et al, 50 which did not quantify the effects of the risk factors. In contrast, we had specifically quantified the effect of four different comorbidities (namely heart failure, respiratory disease, depression, and renal disease) and other patient characteristics which were significantly associated with increased risk of 30-day hospital readmission among adult patients with DM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is the first SR with MA to demonstrate that gender, age, race, health insurance type, comorbidities including heart failure, respiratory disease, depression and renal disease, LOS as well as use of insulin therapy were significantly associated with 30-day unplanned hospital readmission. Our findings are consistent with those reported in a recent SR by Robbins et al, 50 which did not quantify the effects of the risk factors. In contrast, we had specifically quantified the effect of four different comorbidities (namely heart failure, respiratory disease, depression, and renal disease) and other patient characteristics which were significantly associated with increased risk of 30-day hospital readmission among adult patients with DM.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with those reported in a recent SR by Robbins et al , 50 which did not quantify the effects of the risk factors. In contrast, we had specifically quantified the effect of four different comorbidities (namely heart failure, respiratory disease, depression, and renal disease) and other patient characteristics which were significantly associated with increased risk of 30-day hospital readmission among adult patients with DM.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with prior studies of patients with diabetes, 8,38,39 younger patients had a higher risk of readmission compared with older patients once other risk factors for readmission, particularly comorbidities, were accounted for. This may reflect the unique challenges that younger people face when living with a chronic disease.…”
Section: Discussionsupporting
confidence: 79%
“…Another study found that the number of re‐admissions in the past year is related to self‐care behaviour (Linn, Azzolin, & Souza, ). The causes of re‐admission for patients with diabetes can be complicated (La Manna, Bushy, & Gammonley, ) and include comorbidities and age (Robbins, Keung, Sankar, Randeva, & Arvanitis, ). In short, the research findings illustrated the importance of self‐management, which has great potential to reduce re‐admission.…”
Section: Discussionmentioning
confidence: 99%